OPTIMASI KONSENTRASI N-NITRAT PADA KULTIVASI MIKROALGA KULTUR CAMPURAN CHLORELLA SP. DAN SPIRULINA SP. UNTUK MENINGKATKAN KADAR PROTEIN DAN ASTAKSANTIN MENGGUNAKAN MEDIUM LIMBAH CAIR PERIKANAN LELE - Najmi Fathan Mubinna, Muhammad
Fishery wastewater contains organic content, including nitrogen and phosphorus, which promotes the growth of microalgae, making it a potential substitute for commercial media. However, to achieve similar microalgae productivity as commercial media, additional nutrients are required. This study focused on adding the NaNO3 compound to the fishery wastewater medium, aiming for different concentrations of N-Nitrate (23.33 mM, 46.67 mM, and 93.33 mM) while maintaining the control at 75% (v/v) catfish wastewater. The cultivation process involved three stages: initial growth in 800 mL culture bottles for 14 days, followed by a pre-scaling up stage in a Vertical Tubular Reactor with a working volume of 10 L using the optimum N-Nitrate concentration, and finally scaling up in an Open Raceway Pond with a working volume of 38 L. A mixed culture of Chlorella sp. and Spirulina sp. with a 1:1 (v/v) ratio was employed. The study observed various parameters, including cell growth, microalgae biomass productivity, protein content, and astaxanthin levels. Protein levels were measured using the alkaline cell disruption and Bradford methods, while astaxanthin was extracted via maceration and measured with HPLC. The results revealed that N-Nitrate concentration significantly affected (p < 0.05) the growth of Chlorella sp. co-culture cells, biomass productivity, N-Nitrate, and P-Phosphate absorption rates, as well as protein content. However, the co-culture of Spirulina sp. and astaxanthin levels did not demonstrate a significant effect (p > 0.05). The highest protein and astaxanthin levels were achieved at the 23.33 mM concentration, with values of 33.01 ± 3.47% dry weight and 1.471 ± 0.617 ?g/g dry weight, respectively. At this concentration, the microalgae also exhibited the highest cell growth parameters (? and dt in Chlorella sp. co-culture = 0.218 ± 0.013/day and 76.170 ± 4.423 hours, respectively; Spirulina sp. co-culture = 0.153 ± 0.020/day and 108.422 ± 13.091 hours, respectively). The highest biomass productivity was achieved at the 46.67 mM concentration (0.0133 g/L/day). Regarding N and P absorption parameters, the 93.33 mM variation showed the highest N-Nitrate and P-Phosphate uptake rates. The protein content in the mixed culture microalgae Chlorella sp. and Spirulina sp., cultivated in scaling-up at the Open Raceway Pond using the optimum concentration treatment (23.33 mM), did not significantly differ from cultivation in 800 mL culture bottles (39.013 ± 1.4% dry weight).